Loneliness, online learning and student outcomes in college students living with disabilities: results from the National College Health Assessment Spring 2022 - Bevens, William; Stoeckl, Sarah E.; Schueller, Stephen M.; Kim, Jeongmi; Cha, Biblia S.; Chwa, Cindy; Stadnick, Nicole A.; Best, Nakia C.; Sorkin, Dara H. (Frontiers in Psychology, 2024)
Background: People with disabilities face many health, economic and social disparities. Loneliness is recognized as a significant issue for this group however, its impact on students with disabilities (SWDs) remains a critically underexplored area of research. Importantly, as higher education continues its transition to the digital space, the potential to entrench social isolation and loneliness within this population has not been examined. This research seeks to explore the associations between SWDs, loneliness, online learning, and academic outcomes in a national survey of university students. Methods: Using the National College Health Assessment from Spring 2022, this study compared multiple outcomes between different groups of SWDs and students without disabilities. Two ordinal regression models were used to estimate associations between loneliness, disability type and learning mode (online vs in-person), as well as cumulative grade average (CGA) with disability type. Results: All disability types included within this study were positively associated with increased odds of loneliness for those engaged in online learning compared to students without disabilities. Interactions indicate a significant effect of in-person learning compared with online learning for deaf or hard of hearing students, and those with multiple disabilities. Several disability groups reported decreased odds of higher CGA compared to students without disabilities. Conclusions: Loneliness is a significant issue for all SWD groups reported in this study. The impact of disability on academic outcomes is reported herein; however, its impact on medium-to-long term outcomes for these individuals remains unknown. To address inequities in higher education for SWDs, universities must invest more resources to holistically support these students.